Whole genome sequence analysis of Shigella from Malawi identifies fluoroquinolone resistance. Issue 5 (4th May 2021) - Stenhouse, George E.; Jere, Khuzwayo C.; Peno, Chikondi; Bengtsson, Rebecca J.; Chinyama, End; Mandolo, Jonathan; Cain, Amy; Iturriza-Gómara, Miren; Bar-Zeev, Naor; Cunliffe, Nigel A.; Cornick, Jennifer; Baker, Kate S.
Abstract : Increasing antimicrobial resistance and limited alternative treatments have led to fluoroquinolone-resistant Shigella strain inclusion on the WHO global priority pathogens list. In this study we characterized multiple Shigella isolates from Malawi with whole genome sequence analysis, identifying the acquirable fluoroquinolone resistance determinant qnrS1 .